Program Layanan Konsultasi Psikologis pada Penyintas Long Covid-19 - Diny Amenike; Egha Febrianingsih; Sylvia Dewiriza; Haznaz Dhiya Ulhaq Z.N.; Cikita Aidha Putri; Rozi Sastra Purna; Dwi Puspasari; Septi Mayang Sarry; Nila Anggreiny; Meria Susanti; Amatul Firdausa Nasa; Siska Oktari; Yantri Maputra; Tri Rahayuningsih; Fitria Rahmi; Mafaza Mafaza; Izzanil Hidayati; Liliyana Sari (Warta Pengabdian Andalas, 2022)
Survivors of Covid-19 can still experience symptoms such as being still infected with a virus known as Long Covid-19. Covid-19 survivors with long Covid-19 experience physical and psychological disorders. Psychological disorders include cognitive disorders, memory loss, anxiety, sleep disorders, quality of life disorders, and work problems. This problem will undoubtedly impact individual productivity, so it is necessary to carry out a "Long Covid-19 Hotline". This activity aims to provide health services to Covid-19 survivors to overcome their Post-Covid conditions. The Psychologist Team of Psychology Study Program and Respiration and Pulmonology Medical Faculty Universitas Andalas conducted this activity by telephone in September and October 2021. Activities were carried out by providing psychological consultation or further recommendations for participants' psychological complaints. The results of the psychological condition of participants using Generalized Anxiety Disorder (GAD) 7 screening tools showed that the highest complaints were anxiety at 46%, insomnia at 24%, difficulty concentrating at 13%, and depression at 9% and stress at 8%. As for the follow-up results after the consultation, 90% of participants' psychological complaints were reduced, 89% of participants had made follow-up recommendations, and 100% of participants felt this activity was beneficial. Based on a survey of Covid-19 survivors, their psychological condition improved after conducting a Long Covid-19 Hotline.